نشاط الصيد، فرصة للاستثمار وإحداث تنمية محلية - ولاية مستغانم نموذجا -: Fishing activity, an investment opportunity and local development - Mostaganem state as a model - مواعي بحرية; تواتي خديجة (Journal of North African Economies, 2025)
This article addresses the importance of fishing activity as a key driver to emphasize local development, to deploy this on Mostaganem as a coastal state. Its coastline as estimated of 124.5 km and the diversity of its marine resources make the state possess an underlying productive fish wealth. Therefore, that makes it specialized in fishing field & a distinctive motivation to stimulate and encourage investment as a mechanism to support and strengthen fishing sectors’ role in achieving state’s local development. This research paper aims to highlight the most prominent qualifications held by the fishing sector in Mostaganem state upon which can be considered as the basis for investment in fishing activity &also can be considered as domestic attractions for national and foreign investment, especially if it works to improve the state investment environment generally. This study maintained that Mostaganem had received authorities' great attention in regard with the fishing activity promotion and emphasis its role in affecting local development, hence these efforts under this trend could not be denied. But despite of that the lack of completion of its planned endeavor’s still not yet achieved because of many problems that presented themselves and needed complementary plans to contain and address them.